Carbon-nitrogen doped spinel cobalt-iron oxide or alloy hybrid / graphene aerogel electrode material and preparation method and application thereof

By combining CoFe-PBA nanoparticles with graphite oxide and graphene, carbon-nitrogen-doped spinel-type cobalt iron oxide or alloy hybrid/graphene aerogel electrode material is prepared, which solves the problem of limited hydrogen bonding activity of existing non-precious metal catalysts in alkaline electrolytes, and achieves efficient hydrogen production by electrolytic water and excellent stability.

CN115433967BActive Publication Date: 2025-04-04WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211212138.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-04-04
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The existing non-precious metal catalysts have limited hydrogen bonding activity in alkaline electrolytes, making it difficult to effectively catalyze the electrolysis of water to produce hydrogen.

Method used

By combining CoFe-PBA nanoparticles with graphite oxide and graphene, carbon-nitrogen-doped spinel-type cobalt iron oxide or alloy hybrid/graphene aerogel electrode material was prepared, and the atmosphere, temperature and time were controlled by heat treatment to form a plum pudding cake structure with excellent electrochemical properties.

Benefits of technology

Efficient electrochemical energy conversion was achieved, significantly improving hydrogen evolution efficiency and catalytic activity, and the catalytic activity loss was almost negligible after continuous 48 hours of testing, showing excellent stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003875461390000011
    Figure HDA0003875461390000011
  • Figure HDA0003875461390000012
    Figure HDA0003875461390000012
  • Figure HDA0003875461390000021
    Figure HDA0003875461390000021
Patent Text Reader

Abstract

The present invention relates to a carbon-nitrogen doped spinel type cobalt iron oxide or alloy hybrid / graphene aerogel electrode material and its preparation method and application. First, graphite oxide and CoFe-PBA are synthesized, and then CoFe-PBA / GA aerogel is synthesized by hydrothermal reaction; then the aerogel is placed in a nitrogen atmosphere for high temperature heat treatment to obtain CoFe2O4@NC / GA aerogel; the aerogel is placed in a reducing atmosphere for heat treatment at different temperatures for different times to obtain CoFe@NC / GA and CoFe2O4-CoFe@NC / GA aerogels; the three aerogels subjected to high temperature heat treatment are loaded on foam metal in the form of solutions to obtain a series of aerogel electrode materials. The present invention prepares a series of aerogel electrode materials with plum pudding cake structure, the rough and porous graphene aerogel wraps nanoparticles, the rough outer surface provides a higher specific surface area and more active sites to improve the performance, and the holes of different sizes promote mass transfer in the reaction process and improve the efficiency of hydrogen precipitation. The electrode material has good stability and is widely used in the electrolysis of water to produce hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocomposite materials, and in particular to a carbon-nitrogen doped spinel cobalt-iron oxide or alloy hybrid / graphene aerogel electrode material and a preparation method and application thereof. Background Art

[0002] With the advancement of science and technology, people's requirements for quality of life are getting higher and higher, which also makes the demand for energy more intense. The amount of raw materials of non-renewable energy is not enough to support people's strong demand in the long run, and excessive exploitation and utilization will cause a series of environmental problems. Therefore, adjusting the energy structure and making full use of and developing renewable energy have become urgent issues to be solved by many researchers.

[0003] Hydrogen has many advantages, such as high combustion calorific value, clean and pollution-free, and good recyclability. It is considered to be one of the most ideal clean energy sources. Hydrogen production by water electrolysis is a relatively ideal method for hydrogen production. Precious metal catalysts have excellent electrochemical activity and have been used to produce hydrogen by water electrolysis, but their high cost and resource scarcity limit their widespread application. Finding suitable non-precious metal materials and applying them to water electrolysis to produce hydrogen is a difficult problem that many researchers are working to overcome.

[0004] Most non-noble metals have limited HER activity in alkaline electrolytes due to their significantly different hydrogen bonding energies with platinum. To address this issue, another element can be alloyed into the monometallic lattice of a given non-noble metal to improve the electrochemical performance, because the formation of heteroatom bonds can cause ligand effects, and the change in bond length can cause strain effects, which further affect the electrocatalytic water splitting kinetics.

[0005] Spinel metal oxides are oxides composed of two or more metal elements, belonging to ionic compounds and cubic crystal system. The most common and widely studied are metal oxides with AB2O4 spinel structure, where A and B represent different metal elements and O represents oxygen. It can be regarded as a cubic structure of 32 oxygen anions, which will produce 32 octahedral vacancies and 64 tetrahedral vacancies, with A ions and B ions filling the octahedral vacancies and tetrahedral vacancies respectively. Spinel metal oxides are very attractive due to their low cost, abundant earth resources, and excellent magnetic, catalytic and electrical properties. Due to the electronic transition between metals of different valence states at the oxygen site and the additional surface oxidation active metal centers, spinel bimetallic oxides usually show higher electrochemical activity than metal oxides.

[0006] Carbon materials have the advantages of large pore size, large specific surface area, high mass transfer efficiency, and accessible active sites, which provide great opportunities for the construction of new composite catalytic materials with superior performance. Graphene, as a typical carbon material, has gradually become a research hotspot, and various catalysts developed around graphene are widely used in chemical industry, biomedicine and other fields. Aerogel catalysts often have the advantages of large specific surface area and many active sites, and are also very popular.

[0007] Among the many different types of catalyst materials, based on the characteristics of the above materials, the present invention focuses on the preparation and electrocatalytic performance of transition metal materials, aerogel materials and carbon materials. Transition metal materials are used as active substances and combined with three-dimensional carbon materials to prepare functional nanomaterials with excellent electrochemical properties and stability, thereby providing a new approach and method for the preparation of water electrolysis catalysts. Summary of the invention

[0008] One of the purposes of the present invention is to provide a method for preparing a carbon-nitrogen doped spinel cobalt iron oxide / graphene aerogel electrode material, the method mainly comprising the following steps:

[0009] S1, mixing graphite oxide (GO), Prussian blue analog CoFe-PBA nanoparticles, and polyvinyl pyrrolidone (PVP) and uniformly dispersing them by ultrasonication, followed by hydrothermal reaction, cooling, washing, and drying after the reaction to obtain CoFe-PBA / GA aerogel;

[0010] S2, heat treating the CoFe-PBA / GA aerogel in an inert atmosphere to obtain CoFe2O4@NC / GA aerogel;

[0011] S3. Load the CoFe2O4@NC / GA aerogel onto foam metal to obtain a carbon-nitrogen doped spinel cobalt iron oxide / graphene aerogel electrode material.

[0012] Furthermore, the method also includes step S4: placing the CoFe2O4@NC / GA aerogel obtained in step S2 in a reducing atmosphere, and heat treating it at different temperatures for different times to obtain CoFe@NC / GA aerogel and CoFe2O4-CoFe@NC / GA aerogel respectively; loading the CoFe@NC / GA aerogel and CoFe2O4-CoFe@NC / GA aerogel on foam metal respectively to obtain carbon-nitrogen doped spinel cobalt-iron alloy / graphene aerogel electrode material and carbon-nitrogen doped spinel cobalt-iron oxide-alloy hybrid / graphene aerogel electrode material respectively.

[0013] Furthermore, the preparation method of graphite oxide in step S1 is as follows: graphite powder, potassium permanganate, and concentrated sulfuric acid are mixed and reacted, followed by adding hydrogen peroxide and filtering, and the obtained solid is dispersed with dilute hydrochloric acid (mass fraction 5%) and deionized water in turn, and finally solid-liquid separation and drying are performed to obtain graphite oxide. The mass ratio of graphite powder to potassium permanganate is 1:1-1:3, the reaction temperature is 20°C-95°C, and the reaction time is 4.5-6h.

[0014] Furthermore, the preparation method of the Prussian blue analog CoFe-PBA nanoparticles in step S1 is as follows: prepare a potassium ferrocyanide aqueous solution, denoted as solution I; prepare a mixed aqueous solution of cobalt nitrate and trisodium citrate, denoted as solution II; slowly add solution I to solution II, and the resulting mixture is allowed to react at room temperature, and after the reaction, the solid-liquid separation is completed and washed and dried to obtain CoFe-PBA nanoparticles. The molar ratio of potassium ferrocyanide, cobalt nitrate or its hydrate, and trisodium citrate or its hydrate required for the reaction is 1:1:1-4:6:9. Prussian blue analog (PBA) is selected as a raw material because it has an open skeleton structure, a large specific surface area, and a uniform catalytic center. It can also provide a carbon source and a nitrogen source for the carbon-nitrogen doped structure during the annealing process. PBA can adjust the electronic structure of the surface active center in this process, thereby improving the electrocatalytic activity of the material.

[0015] Furthermore, the specific process of step S1 is as follows: first prepare a graphite oxide dispersion, then add CoFe-PBA and PVP and stir evenly, place the resulting mixture at 180-200°C for hydrothermal reaction for 10-12h, cool naturally and wash repeatedly with deionized water, and finally freeze-dry. The mass ratio of graphite oxide, CoFe-PBA, and PVP is 1:1:1-16:2:1. Graphene aerogel has a larger specific surface area, mainly providing carbon layer protection, and also providing more active sites as a place for in-situ growth of spinel transition metal oxides, while also improving the electrocatalytic performance of the material.

[0016] Furthermore, the heat treatment in step S2 is carried out in a tubular furnace, the heating rate is 5-7°C / min, the heat treatment temperature is 300-600°C, the heat treatment time is 1-2h, and the inert atmosphere is nitrogen or argon.

[0017] Furthermore, the foam metal in steps S3 and S4 is selected from any one of foam nickel and foam copper, and the foam metal needs to be pretreated before loading, and the pretreatment includes acid washing, alcohol washing, water washing, drying, etc.

[0018] Furthermore, the loading process of steps S3 and S4 is specifically as follows: the aerogel to be loaded is prepared into a dispersion liquid, the dispersion liquid is dropped on the foam metal, and the dispersion liquid is fully dried at room temperature.

[0019] Furthermore, the heat treatment in step S4 is carried out in a tube furnace, and the reducing atmosphere is a mixture of Ar and H2, wherein the volume fraction of H2 is 5%. During the heat treatment, the original CoFe2O4@NC is reorganized and grows in situ in the GA with a large number of porous structures, forming a heterogeneous structure of alloy-connected carbon materials.

[0020] Furthermore, in step S4, the heating rate for preparing CoFe@NC / GA aerogel is 5-7°C / min, the heat treatment temperature is 500-800°C, and the heat treatment time is 1-2h; the heating rate for preparing CoFe2O4-CoFe@NC / GA aerogel is 5-7°C / min, the heat treatment temperature is 800-900°C, and the heat treatment time does not exceed 1h.

[0021] The second object of the present invention is to provide a carbon-nitrogen doped spinel type cobalt iron oxide or alloy hybrid / graphene aerogel electrode material, which actually includes three types, namely CoFe2O4@NC / GA aerogel loaded foam metal, CoFe@NC / GA aerogel loaded foam metal, and CoFe2O4-CoFe@NC / GA aerogel loaded foam metal. These three aerogels all present a plum pudding cake structure. The graphene aerogel of CoFe2O4@NC / GA wraps bimetallic nanoparticles. There are holes of different sizes on the graphene, which can promote the overflow of bubbles and facilitate the mass transfer process. The rough surface of the carbon-nitrogen doped bimetallic nanoparticles is evenly distributed with smaller nanoparticles, and this rough surface can provide a larger specific surface area. The morphology of CoFe@NC / GA and CoFe2O4-CoFe@NC / GA is similar to that of CoFe2O4@NC / GA, but their bimetallic nanoparticles have smoother surfaces.

[0022] The third object of the present invention is to provide an application of the above-mentioned carbon-nitrogen doped spinel cobalt-iron oxide or alloy hybrid / graphene aerogel electrode material in hydrogen production by electrolysis of water.

[0023] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:

[0024] (1) The present invention obtains three different electrode materials by controlling the atmosphere, temperature and time of heat treatment. These electrode materials have unique plum pudding model structure, large surface area, excellent air permeability, high electronic conductivity and carbon-nitrogen doped structure and composite characteristics of carbon material substrate, which work together to promote the oxygen evolution reaction (OER) process.

[0025] (2) The present invention uses graphite oxide and CoFe-PBA as raw materials, and provides a new approach for the transformation of the chemical composition and structural components of transition metal compounds and for the formation of a three-dimensional network heterostructure with porous carbon materials to achieve efficient electrochemical energy conversion.

[0026] (3) The aerogel prepared by the present invention has a three-dimensional porous structure, which can inhibit the stacking of graphene sheets, and the surface of graphene contains abundant active sites, thus significantly improving the hydrogen evolution efficiency.

[0027] (4) The CoFe2O4-CoFe@NC / GA prepared in the present invention exhibits better performance than the electrolytic cell composed of commercial Pt / C and RuO2. After 48 hours of continuous testing, the loss of its catalytic activity is almost negligible, showing excellent stability, which has a good promoting effect on promoting the development of non-precious metal alkaline water electrolysis catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a scanning electron microscope image of CoFe-PBA in Example 1 of the present invention;

[0029] Figure 2 This is a scanning electron microscope image of CoFe2O4@NC / GA-500 in Example 1 of the present invention;

[0030] Figure 3 X-ray diffraction patterns of CoFe-PBA / GA and CoFe2O4@NC / GA in Example 1 of the present invention;

[0031] Figure 4 This is a test diagram of the hydrogen evolution performance of CoFe@NC / GA-800 in Example 2 of the present invention;

[0032] Figure 5 This is the X-ray photoelectron spectrum of CoFe2O4-CoFe@NC / GA-800 to N1s in Example 3 of the present invention;

[0033] Figure 6 This is a stability test curve diagram of CoFe2O4-CoFe@NC / GA-800 in Example 3 of the present invention. DETAILED DESCRIPTION

[0034] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.

[0035] Example 1

[0036] S1. Put 5g of graphite powder, 15g of potassium permanganate and a magnet into a 500mL three-necked flask, place the flask in an ice-water bath, slowly add 115mL of concentrated sulfuric acid and stir for 2h. After the mixture in the flask is heated to 35°C, continue to stir and react for 2h, then slowly add 230mL of deionized water, and continue to react for 30min after the mixture in the flask is heated to 95°C. After the reaction is completed, slowly add an appropriate amount of hydrogen peroxide, and the color of the solution turns golden yellow. After filtering, mix and wash the filter residue with an appropriate amount of dilute hydrochloric acid (mass fraction 5%), let it stand fully, and then centrifuge to remove the residue, then add an appropriate amount of deionized water, wash repeatedly, let it stand, and then centrifuge. Finally, place the solid obtained by centrifugation in a vacuum freeze dryer, freeze-dry to constant weight at -80°C, and obtain brown GO powder for standby.

[0037] S2. Add 4.0mmol potassium ferricyanide (K3[Fe(CN)6]) to 200mL deionized water, dissolve and disperse it evenly by ultrasound, and obtain yellow solution I. Add 6.0mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 9.0mmol trisodium citrate dihydrate (Na3C6H5O7·2H2O) to 200mL deionized water, dissolve and disperse it evenly by ultrasound, and obtain solution II. While stirring, slowly add solution I to solution II, continue stirring for 1 minute after the addition, and place the resulting suspension in a constant temperature environment of 25°C for 24 hours. The obtained purple-gray liquid is transported to a medium-speed centrifuge for centrifugation, collect the purple precipitate and wash it several times with deionized water and anhydrous ethanol, then place it in a vacuum drying oven and dry it at 60°C for 6 hours, and finally obtain a purple-gray powder, which is CoFe-PBA nanoparticles.

[0038] S3. Weigh 2g GO powder with a balance and place it in a beaker, then add 500mL deionized water and ultrasonically disperse it evenly to obtain a GO dispersion with a concentration of 4g / L. Use a pipette to draw 20mL GO dispersion and add it to a small glass bottle with a capacity of 25mL, then add 10mg CoFe-PBA nanoparticles and 5mg PVP, and ultrasonically disperse it evenly to obtain a brown colloidal solution. Transfer the small glass bottle to a polytetrafluoroethylene-lined autoclave, heat it to 180℃ in a muffle furnace for a constant temperature hydrothermal reaction for 12 hours, and cool it naturally after the reaction to obtain a black jelly-like hydrogel. Wash it repeatedly with deionized water several times to remove the residue, then place it in an ultra-low temperature refrigerator for freezing and solidification, and then transfer it to a vacuum freeze dryer for freeze drying to constant weight, and finally obtain CoFe-PBA / GA aerogel.

[0039] The collected CoFe-PBA / GA aerogel was placed in a tubular furnace under N2 protective atmosphere, heated to 500°C at a heating rate of 5°C / min, sintered at this temperature for 2 hours, and cooled in the furnace to obtain CoFe2O4@NC / GA-500 aerogel.

[0040] S4, weigh 4mg CoFe2O4@NC / GA-500 aerogel and 1mg Ketjen black with a 1 / 10,000 balance and place them in a centrifuge tube with a capacity of 2mL, use a pipette to measure 500μL deionized water, 500μL anhydrous ethanol and 20μL nafion membrane solution (5wt%) and drop them into the centrifuge tube, place the centrifuge tube in an ultrasonic instrument for ultrasonic dispersion, and form a homogeneous dispersion for use. At the same time, cut the nickel foam into 1cm×2cm strips, wash with 3mol / L hydrochloric acid, deionized water and anhydrous ethanol in turn to remove surface impurities, and then dry for use. 500μL of the above homogeneous dispersion is dripped drop by drop on the treated nickel foam surface, and then fully dried at room temperature to finally obtain the target sample CoFe2O4@NC / GA-500 aerogel electrode material.

[0041] The CoFe-PBA nanoparticles, CoFe-PBA / GA aerogel, and CoFe2O4@NC / GA-500 aerogel prepared in Example 1 were sampled and tested. The results are as follows: Figure 1-3 As shown. Figure 1 This is a scanning electron microscope image of CoFe-PBA. It can be seen from the image that the CoFe-PBA nanoparticles are uniformly embedded in the three-dimensional network structure of graphene aerogel and are completely covered by graphene, and the surface is full of wrinkles.

[0042] Figure 2 This is a scanning electron microscope image of CoFe2O4@NC / GA-500 aerogel. It can be seen that the surface of CoFe2O4 nanoparticles doped with nitrogen and carbon is rougher than that of CoFe-PBA nanoparticles. The surface of the nitrogen-carbon doped nanoparticles is evenly distributed with smaller nanoparticles, which is caused by the in-situ carbon-nitrogen doping formed after the cyanide group of the CoFe-PBA nanoparticles breaks and loses bound water. This rough surface can provide a larger specific surface area and more active sites, which is conducive to the improvement of catalytic performance. The increase of various pores enhances the mass transfer capacity during the catalytic reaction, thereby improving the bubble overflow efficiency, which also improves the catalytic performance of the catalyst to a certain extent.

[0043] Figure 3The XRD spectra of CoFe-PBA / GA aerogel (②) and CoFe2O4@NC / GA (④) are shown in Figure 2. The characteristic peaks of the two aerogels have changed significantly, which indicates that CoFe-PBA is converted into other substances after reacting at 500°C in a nitrogen environment for two hours. After careful analysis, it was found that several new obvious diffraction peaks appeared in the XRD spectrum of CoFe2O4@NC / GA aerogel, which are located at 30.12°, 35.45°, 27.07° and 43.08°, corresponding to the (200), (311), (222) and (400) crystal planes of CoFe2O4 (PDF#23-986).

[0044] Example 2

[0045] S1. Put 5g of graphite powder, 15g of potassium permanganate and a magnet into a 500mL three-necked flask, place the flask in an ice-water bath, slowly add 115mL of concentrated sulfuric acid and stir for 2h. After the mixture in the flask is heated to 35°C, continue to stir and react for 2h, then slowly add 230mL of deionized water, and continue to react for 30min after the mixture in the flask is heated to 95°C. After the reaction is completed, slowly add an appropriate amount of hydrogen peroxide, and the color of the solution turns golden yellow. After filtering, mix and wash the filter residue with an appropriate amount of dilute hydrochloric acid (mass fraction 5%), let it stand fully, and then centrifuge to remove the residue, then add an appropriate amount of deionized water, wash repeatedly, let it stand, and then centrifuge. Finally, place the solid obtained by centrifugation in a vacuum freeze dryer, freeze-dry to constant weight at -80°C, and obtain brown GO powder for standby.

[0046] S2, 4.0mmol potassium ferricyanide was added to 200mL deionized water, ultrasonically dissolved and evenly dispersed to obtain yellow solution I. 6.0mmol cobalt nitrate hexahydrate and 9.0mmol trisodium citrate dihydrate were added to 200mL deionized water, ultrasonically dissolved and evenly dispersed to obtain solution II. Solution I was slowly added dropwise to solution II while stirring, and stirring was maintained for 1 minute after the addition was completed. The resulting suspension was placed in a 25°C constant temperature environment and allowed to stand for 24 hours. The obtained purple-gray liquid was transported to a medium-speed centrifuge for centrifugation, and the purple precipitate was collected and washed several times with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven and dried at 60°C for 6 hours to finally obtain a purple-gray powder, which was CoFe-PBA nanoparticles.

[0047] S3. Weigh 2g GO powder with a balance and place it in a beaker, then add 500mL deionized water and ultrasonically disperse it evenly to obtain a GO dispersion with a concentration of 4g / L. Use a pipette to draw 20mL GO dispersion and add it to a small glass bottle with a capacity of 25mL, then add 10mg CoFe-PBA nanoparticles and 5mg PVP, and ultrasonically disperse it evenly to obtain a brown colloidal solution. Transfer the small glass bottle to a polytetrafluoroethylene-lined autoclave, heat it to 180℃ in a muffle furnace for a constant temperature hydrothermal reaction for 12 hours, and cool it naturally after the reaction to obtain a black jelly-like hydrogel. Wash it repeatedly with deionized water several times to remove the residue, then place it in an ultra-low temperature refrigerator for freezing and solidification, and then transfer it to a vacuum freeze dryer for freeze drying to constant weight, and finally obtain CoFe-PBA / GA aerogel.

[0048] The collected CoFe-PBA / GA aerogel was placed in a tubular furnace under N2 protective atmosphere, heated to 600°C at a heating rate of 7°C / min, sintered at this temperature for 2 hours, and cooled in the furnace to obtain CoFe2O4@NC / GA-600 aerogel.

[0049] S4. The collected CoFe2O4@NC / GA-600 aerogel was placed in a tubular furnace under an Ar / H2 (5%) atmosphere, and sintered at 800°C for 2 h at a heating rate of 3°C / min. After sintering, the aerogel was cooled with the furnace to obtain a CoFe@NC / GA-800 catalyst.

[0050] S5, weigh 4mg CoFe@NC / GA-800 catalyst and 1mg Ketjen black with a 1 / 10,000 balance and place them in a centrifuge tube with a capacity of 2mL, use a pipette to measure 500μL deionized water, 500μL anhydrous ethanol and 20μL nafion membrane solution (5wt%) and drop them into the centrifuge tube, place the centrifuge tube in an ultrasonic instrument for ultrasonic dispersion, and form a homogeneous dispersion for use. At the same time, cut the nickel foam into 1cm×2cm strips, wash with 3mol / L hydrochloric acid, deionized water and anhydrous ethanol in turn to remove surface impurities, and then dry for use. 500μL of the above homogeneous dispersion is dripped drop by drop on the treated nickel foam surface, and then fully dried at room temperature to finally obtain the target sample CoFe@NC / GA-800 aerogel electrode material.

[0051] The samples were sampled and LSV tests were performed at a fixed scan rate of 2 mV / s. The overpotentials of the target sample CoFe@NC / GA-800 prepared in Example 2 and the related control samples at different current densities were tested. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that at a current density of 10 mA cm -2When the voltage of CoFe@NC / GA-800 is 135mV, the overpotential of CoFe@NC / GA-800 is lower than that of the alloy composite graphene aerogel electrode material prepared by reaction at other temperatures. Analysis shows that the high electrochemical activity of CoFe@NC / GA-800 is due to the plum pudding cake structure composed of porous three-dimensional graphene aerogel and nanoparticles. This structure can expose the catalytic active sites to the greatest extent and promote the improvement of mass transfer efficiency and conductivity efficiency.

[0052] Example 3

[0053] S1. Put 5g of graphite powder, 15g of potassium permanganate and a magnet into a 500mL three-necked flask, place the flask in an ice-water bath, slowly add 115mL of concentrated sulfuric acid and stir for 2h. After the mixture in the flask is heated to 35°C, continue to stir and react for 2h, then slowly add 230mL of deionized water, and continue to react for 30min after the mixture in the flask is heated to 95°C. After the reaction is completed, slowly add an appropriate amount of hydrogen peroxide, and the color of the solution turns golden yellow. After filtering, mix and wash the filter residue with an appropriate amount of dilute hydrochloric acid (mass fraction 5%), let it stand fully, and then centrifuge to remove the residue, then add an appropriate amount of deionized water, wash repeatedly, let it stand, and then centrifuge. Finally, place the solid obtained by centrifugation in a vacuum freeze dryer, freeze-dry to constant weight at -80°C, and obtain brown GO powder for standby.

[0054] S2, 4.0mmol potassium ferricyanide was added to 200mL deionized water, ultrasonically dissolved and evenly dispersed to obtain yellow solution I. 6.0mmol cobalt nitrate hexahydrate and 9.0mmol trisodium citrate dihydrate were added to 200mL deionized water, ultrasonically dissolved and evenly dispersed to obtain solution II. Solution I was slowly added dropwise to solution II while stirring, and stirring was maintained for 1 minute after the addition was completed. The resulting suspension was placed in a 25°C constant temperature environment and allowed to stand for 24 hours. The obtained purple-gray liquid was transported to a medium-speed centrifuge for centrifugation, and the purple precipitate was collected and washed several times with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven and dried at 60°C for 6 hours to finally obtain a purple-gray powder, which was CoFe-PBA nanoparticles.

[0055] S3. Weigh 2g GO powder with a balance and place it in a beaker, then add 500mL deionized water and ultrasonically disperse it evenly to obtain a GO dispersion with a concentration of 4g / L. Use a pipette to draw 20mL GO dispersion and add it to a small glass bottle with a capacity of 25mL, then add 10mg CoFe-PBA nanoparticles and 5mg PVP, and ultrasonically disperse it evenly to obtain a brown colloidal solution. Transfer the small glass bottle to a polytetrafluoroethylene-lined autoclave, heat it to 180℃ in a muffle furnace for a constant temperature hydrothermal reaction for 12 hours, and cool it naturally after the reaction to obtain a black jelly-like hydrogel. Wash it repeatedly with deionized water several times to remove the residue, then place it in an ultra-low temperature refrigerator for freezing and solidification, and then transfer it to a vacuum freeze dryer for freeze drying to constant weight, and finally obtain CoFe-PBA / GA aerogel.

[0056] The collected CoFe-PBA / GA aerogel was placed in a tubular furnace under N2 protective atmosphere, heated to 500°C at a heating rate of 6°C / min, sintered at this temperature for 2 hours, and cooled in the furnace to obtain CoFe2O4@NC / GA-500 aerogel.

[0057] S4. The collected CoFe2O4@NC / GA-500 aerogel was placed in a tubular furnace under an Ar / H2 (5%) atmosphere, heated to 800°C at a heating rate of 5°C / min, and sintered at this temperature for 1 hour. After sintering, the aerogel was cooled with the furnace to obtain a CoFe2O4-CoFe@NC / GA-800 catalyst.

[0058] S5, weigh 4mg CoFe2O4-CoFe@NC / GA-800 catalyst and 1mg Ketjen black with a 1 / 10,000 balance and place them in a centrifuge tube with a capacity of 2mL, measure 500μL deionized water, 500μL anhydrous ethanol and 20μL nafion membrane solution (5wt%) with a pipette and drop them into the centrifuge tube, place the centrifuge tube in an ultrasonic instrument for ultrasonic dispersion, and form a homogeneous dispersion for standby use. At the same time, cut the nickel foam into 1cm×2cm strips, wash with 3mol / L hydrochloric acid, deionized water and anhydrous ethanol in turn to remove surface impurities, and then dry for standby use. 500μL of the above homogeneous dispersion is dripped drop by drop on the treated nickel foam surface, and then fully dried at room temperature to finally obtain the target sample CoFe2O4-CoFe@NC / GA-800 aerogel electrode material.

[0059] The CoFe2O4-CoFe@NC / GA-800 aerogel prepared in Example 3 was sampled and tested. The results are as follows: Figure 5-6 As shown. Figure 5The X-ray photoelectron spectroscopy (XPS) analysis of N1s shown in the figure shows that the characteristic peaks at binding energies of 398.1 eV, 400.1 eV and 401.0 eV correspond to pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen structures, respectively. Most of the pyrrolic nitrogen content can be attributed to the introduction of PVP during the catalyst synthesis process, the graphitic nitrogen confirms the successful doping of nitrogen during the high temperature treatment, and the presence of pyridinic nitrogen is beneficial to improve the catalytic performance of the catalyst.

[0060] The stability of CoFe2O4-CoFe@NC / GA-800 aerogel is shown in Figure 6 In this test, the CoFe2O4-CoFe@NC / GA||CoFe2O4-CoFe@NC / GA electrode was -2 Under a constant current density, after 48 hours of stability test, its voltage value hardly dropped and the performance was very stable.

Claims

1. A method for preparing a carbon-nitrogen doped spinel cobalt iron oxide / graphene aerogel electrode material, characterized in that The method comprises the following steps: S1, mixing graphite oxide, Prussian blue analog CoFe-PBA nanoparticles and PVP, and then uniformly dispersing them by ultrasonication, followed by hydrothermal reaction, and finally separating and purifying to obtain CoFe-PBA / GA aerogel; S2, heat treating the CoFe-PBA / GA aerogel in an inert atmosphere to obtain CoFe2O4@NC / GA aerogel; S3, loading CoFe2O4@NC / GA aerogel onto foam metal to obtain carbon-nitrogen doped spinel cobalt iron oxide / graphene aerogel electrode material; S4, placing the CoFe2O4@NC / GA aerogel prepared in S2 in a reducing atmosphere, and heat treating it at different temperatures for different times to obtain CoFe@NC / GA aerogel and CoFe2O4-CoFe@NC / GA aerogel respectively; loading the CoFe@NC / GA aerogel and CoFe2O4-CoFe@NC / GA aerogel on foam metal respectively to obtain carbon-nitrogen doped spinel cobalt-iron alloy / graphene aerogel electrode material and carbon-nitrogen doped spinel cobalt-iron oxide-alloy hybrid / graphene aerogel electrode material. Aerogel electrode material; wherein the heating rate for preparing CoFe@NC / GA aerogel is 5-7°C / min, the heat treatment temperature is 500-800°C, and the heat treatment time is 1-2h; the heating rate for preparing CoFe2O4-CoFe@NC / GA aerogel is 5-7°C / min, the heat treatment temperature is 800-900°C, and the heat treatment time does not exceed 1h; the heat treatments in steps S3 and S4 are both carried out in a tubular furnace, and the reducing atmosphere is a mixture of Ar and H2, wherein the volume fraction of H2 is 5%.

2. The preparation method according to claim 1, characterized in that The preparation method of graphite oxide in step S1 is as follows: graphite powder, potassium permanganate and concentrated sulfuric acid are mixed for reaction, then hydrogen peroxide is added and filtered, the obtained solid is dispersed with dilute hydrochloric acid and deionized water in turn, and finally solid-liquid separation and drying are carried out to obtain graphite oxide; wherein the mass ratio of graphite powder to potassium permanganate is 1:1-1:3, the reaction temperature is 20°C-95°C, and the reaction time is 4.5-6h; the preparation method of Prussian blue analog CoFe-PBA nanoparticles in step S1 is as follows: potassium ferrocyanide aqueous solution is slowly added to a mixed aqueous solution of cobalt nitrate and trisodium citrate, the obtained mixture is allowed to stand at room temperature for reaction, separated and purified, and CoFe-PBA nanoparticles are obtained; wherein the molar ratio of potassium ferrocyanide, cobalt nitrate or its hydrate, and trisodium citrate or its hydrate is 1:1:1-4:6:

9.

3. The preparation method according to claim 1, characterized in that: The specific process in step S1 is as follows: first prepare a graphite oxide dispersion, then add CoFe-PBA and PVP and stir evenly, place the resulting mixture at 180-200° C. for hydrothermal reaction for 10-12 hours, cool naturally and wash repeatedly with deionized water, and finally freeze-dry; wherein the mass ratio of graphite oxide, CoFe-PBA and PVP is 1:1:1-16:2:

1.

4. The preparation method according to claim 1, characterized in that: In step S2, the heat treatment is carried out in a tube furnace, the heating rate is 5-7°C / min, the heat treatment temperature is 300-600°C, the heat treatment time is 1-2h, and the inert atmosphere is nitrogen or argon.

5. The preparation method according to claim 1, characterized in that: The foam metal is selected from any one of foam nickel and foam copper. The foam metal needs to be pretreated before loading, and the pretreatment includes acid washing, alcohol washing, water washing, and drying.

6. The preparation method according to claim 1, characterized in that: The specific process of S3 and S4 loading is: prepare the aerogel to be loaded into a dispersion liquid, drop the dispersion liquid on the foam metal, and fully dry it at room temperature.

7. A carbon-nitrogen doped spinel cobalt-iron oxide or alloy hybrid / graphene aerogel electrode material, characterized in that: The electrode material includes CoFe2O4@NC / GA aerogel-loaded foam metal, CoFe@NC / GA aerogel-loaded foam metal, and CoFe2O4-CoFe@NC / GA aerogel-loaded foam metal, all of which present a plum pudding cake structure and are prepared according to any one of claims 1-6.

8. Use of the carbon-nitrogen doped spinel cobalt-iron oxide or alloy hybrid / graphene aerogel electrode material according to claim 7 in hydrogen production by water electrolysis.